2008
DOI: 10.1158/1078-0432.ccr-08-0499
|View full text |Cite
|
Sign up to set email alerts
|

Endosialin Protein Expression and Therapeutic Target Potential in Human Solid Tumors: Sarcoma versus Carcinoma

Abstract: Purpose: Endosialin/CD248/tumor endothelial marker 1is expressed in stromal cells, endothelial cells, and pericytes in various tumors; however, few studies have focused on expression in malignant cells. Experimental Design: We studied expression of endosialin in clinical specimens, cell culture, and animal models and designed an anti-endosialin therapeutic prototype. Results: Fifty human tumor cell lines and 6 normal cell types in culture were assayed by reverse transcription-PCR and/or flow cytometry for endo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
118
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(124 citation statements)
references
References 30 publications
6
118
0
Order By: Relevance
“…The A673 cell line was described in 1973 as being from a patient with a possible rhabdomyosarcoma; however, recent cytogenetic testing and molecular profiling established that A673 cells express the EWS/FLI1 transcription factor and confirmed that A673 cells are Ewing sarcoma (Figure 1). 17–19 A673 cells grown as a human tumor xenograft in immunodeficient mice have proven to be a useful in vivo model to explore the biology of tumor growth and to identify therapeutic targets for sarcomas.…”
Section: Ewing/pnet Sarcoma Model Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…The A673 cell line was described in 1973 as being from a patient with a possible rhabdomyosarcoma; however, recent cytogenetic testing and molecular profiling established that A673 cells express the EWS/FLI1 transcription factor and confirmed that A673 cells are Ewing sarcoma (Figure 1). 17–19 A673 cells grown as a human tumor xenograft in immunodeficient mice have proven to be a useful in vivo model to explore the biology of tumor growth and to identify therapeutic targets for sarcomas.…”
Section: Ewing/pnet Sarcoma Model Systemsmentioning
confidence: 99%
“…In 2005, Dolznig et al showed expression of endosialin transcript in sarcomas, and expression of the protein in malignant cells in one malignant fibrous histiocytoma and one liposarcoma 53. More recently, endosialin protein expression was assessed by immunohistochemistry in 250 clinical specimens of human cancer, including 20 cancer subtypes 19. The results showed that endosialin protein is frequently found in human cancers.…”
Section: Sarcoma Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Endosialin/CD248/TEM1, a transmembrane glycoprotein expressed on pericytes and fibroblasts during tissue development and present in the adult in several mesenchymal cell types, is associated with tumor neovascularization and inflammation and has emerged as a molecular marker and therapeutic target for sarcoma (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). First recognized as the antigen of an antibody raised in mice against human fetal fibroblasts (FB5), endosialin was found to be expressed by human solid tumor vasculature (13) and was detected in a subset of cells enriched for endothelium via selection with P1H12, an anti-CD146 antibody, from a colorectal tumor specimen (14).…”
Section: Introductionmentioning
confidence: 99%
“…Staining intensity was scored on the scale 0, 1ĂŸ, 2ĂŸ, 3ĂŸ. All nine sarcoma subtypes tested included specimens with at least 50% immunoreactive tissue components positive with a minimum of 2ĂŸ staining intensity, indicating the high prevalence of endosialin in sarcomas (12). A retrospective analysis of diagnostic reports showed that endosialin can be detected in high-grade disease and metastasis.…”
Section: Introductionmentioning
confidence: 99%